Effect of temporary calf removal numbers in timed artificial insemination protocols on weaning weight from nelore calves - Carneiro, Luisa Cunha [UNESP] (2013)
This study was conducted to evaluate the effect on the weaning weight of Nelore calves from two factors: the number of times the calves were temporarily removed from their mothers during a timed artificial insemination (TAI), and the month of birth. Attention was given to any possible interaction between these factors. Suckled beef Nelore cows (n= 271) with more than 30 days postpartum were synchronized to a TAI protocol as follows: Day 0: insertion of intravaginal progesterone device ± 2.0 mg of estradiol benzoate; Day 7: application of 12.5 mg of dinoprost tromethamine; Day 9: removal of progesterone device ± 1.0 mg of estradiol cypionate ± temporary calf removal (TCR); Day 11: TAI ± return of the calves to cows. The calves whose mothers conceived after the first insemination were subjected to TCR once, those found empty after 30 days were resynchronized and inseminated according to the TAI protocol and thus, their calves were subjected to TCR a second time. The weaning weight was adjusted to 210 days. Statistical variance analysis was performed by SAS statistics program. It was observed that there was no effect from the number of removals on the weaning weight (P > 0.05); on the other hand, the month of birth did affect it (P < 0.05). In conclusion, the number of TCŔs for TAI protocols during the breeding season did not impact the weaning weight of the calves. However, the month of birth did affect the weaning weight of beef calves, since those born at the beginning of the birth season were heavier.